Gamification of interactive learning using android mobile application for business mathematics/ Ting Su Ung ... [et al.] - Ting, Su Ung; Leong, Yii Ming; Hiong, Kelvin Goh Tee; Ling, Christina Eu Nguk; Khium, Chen Chee (2023)
Many students frequently encounter difficulties while dealing with the concepts of simple interest, compound interest, and annuity in the field of Business Mathematics. Consequently, a novel mobile application, SCI-A, has been created with the aim of augmenting students' comprehension of these subjects. Every question inside the SCI-A framework is intentionally crafted to include a comprehensive solution upon request. This functionality would allow users to recognize and correct their errors as they advance in each subject matter. A preliminary investigation was undertaken at UiTM Sarawak Branch, encompassing six students pursuing a diploma and 21 students pursuing a degree, all of whom were enrolled in the Business Mathematics course. The findings of the study reveal that a majority of students regarded the SCI-A mobile application is user-friendly, entertaining, and capable of enhancing their learning experience, comprehension, and understanding. SCI-A has the potential to serve as a source of motivation for users to engage in other learning endeavours. This application aligns with the fourth Sustainable Development Goal (SDG4), which aims to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all individuals.